Foucauldian surveillance in Dave Eggers’ The Circle - Zahra, Hasanain Riyadh Abdul; Zainal, Zainor Izat; Awang, Mohammad Ewan; Singh, Hardev Kaur Jujar (PalArch Foundation, 2020)
This essay presents a Foucauldian reading of Dave Eggers’s The Circle (2013). The novel portrays power manipulation and disciplinary practices on the subjects who are confined to cellular spaces and are subjected to surveillance gaze. The Circle institution places its workers under constant monitoring and transgress their freedom and privacy by deceiving them with the culture of translucence. According to Foucault, disciplinary power such as surveillance works as\ a technique that converts an individual into an obedient human characterized as a productive and submissive body. In this study, the researchers attempt to investigate Dave Eggers’ The Circle 2013) from the Foucauldian lens, considering his concept of surveillance as an effective disciplinary technique to convert individuals into productive docile bodies and to what extent this notion is accomplished in this novel. The response of the characters to surveillance in The Circle reveals the impact of power manipulation in converting the individual into an obedient subject. Surveillance is displayed as repressive and not only as productive or profitable. The novel reveals in the beginning that the technique of surveillance seeming is harmless to human behaviour, but eventually, it becomes ultimately transgress freedom of humans by highlighting a culture of translucence. The Circle's organisation deceives its customers and employees and makes them abandon their old lives voluntarily and adopt a new shallow and unsatisfactory system.